Integration of DNA Repair, Antigenic Variation, Cytoadhesion, and Chance in Babesia Survival: A Perspective - Allred, David R. (Frontiers in Cellular and Infection Microbiology, 2022)
Apicomplexan parasites live in hostile environments in which they are challenged chemically and their hosts attempt in many ways to kill them. In response, the parasites have evolved multiple mechanisms that take advantage of these challenges to enhance their survival. Perhaps the most impressive example is the evolutionary co-option of DNA repair mechanisms by the parasites as a means to rapidly manipulate the structure, antigenicity, and expression of the products of specific multigene families. The purpose of variant proteins that mediate cytoadhesion has long been thought to be primarily the avoidance of splenic clearance. Based upon known biology, I present an alternative perspective in which it is survival of the oxidative environment within which Babesia spp. parasites live that has driven integration of DNA repair, antigenic variation, and cytoadhesion, and speculate on how genome organization affects that integration. This perspective has ramifications for the development of parasite control strategies.